2017
DOI: 10.3390/rs9100989
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Characteristics of Urban Heat Islands (UHIs) in Northern West Siberian Cities

Abstract: Anthropogenic heat and modified landscapes raise air and surface temperatures in urbanized areas around the globe. This phenomenon is widely known as an urban heat island (UHI). Previous UHI studies, and specifically those based on remote sensing data, have not included cities north of 60 • N. A few in situ studies have indicated that even relatively small cities in high latitudes may exhibit significantly amplified UHIs. The UHI characteristics and factors controlling its intensity in high latitudes remain la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…where, T u and T s are mean temperatures of the urban area and the surrounding areas of the urban area, respectively (See Equation (1)). We have excluded the water bodies while calculating UHI intensity because they can influence the temperature significantly [21]. For calculating the seasonal average temperature, spring was defined as March-May, summer as June-August, autumn as September-November, and winter as December-February [18,29].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…where, T u and T s are mean temperatures of the urban area and the surrounding areas of the urban area, respectively (See Equation (1)). We have excluded the water bodies while calculating UHI intensity because they can influence the temperature significantly [21]. For calculating the seasonal average temperature, spring was defined as March-May, summer as June-August, autumn as September-November, and winter as December-February [18,29].…”
Section: Methodsmentioning
confidence: 99%
“…Jin et al [20] used Moderate Resolution Imaging Spectroradiometer (MODIS) images to identify the differences in surface temperature between the urban and suburban areas of Beijing, New York, and Phoenix, but were unable to identify the UHI change trends because they performed single-year analysis instead of long-term analysis. In the study of Asian mega cities by Tran et al [14] and in that of northwest Siberia by Miles and Esau [21], the change in UHI intensity based on the season and its correlation with related variables were verified using MODIS images. Zhou et al [9] analyzed the difference in UHI intensity based on the area of each city using MODIS images.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…These works did not have their focus on the high latitudes, and therefore include only a few arctic cities (found above 63 • N) in their analysis. A regional study of West Siberian cities was reported in Miles and Esau (2017). This study utilized the LST data product from the MODerate resolution Imaging Spectroradiometer (MODIS).…”
Section: Introductionmentioning
confidence: 99%